1993
DOI: 10.1113/expphysiol.1993.sp003671
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increasing cell length on auxotonic contractions; membrane potential and intracellular calcium transients in single guinea‐pig ventricular myocytes

Abstract: SUMMARYUntil recently the investigation of length-dependent effects in cardiac muscle was restricted to multicellular preparations. We describe our experimental set-up which for the first time, in single cardiac myocytes, permits the effects of changes in cell length on auxotonic contractions (measured by carbon fibre transducers) to be simultaneously recorded with the effects on membrane potential and/or changes in intracellular calcium concentration (using indo-1 AM, acetoxylmethyl form). Consistent with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 27 publications
4
63
1
Order By: Relevance
“…It has been shown that in ferret, cat and rat myocardium [18,22] and isolated Guinea-pig and rat myocytes [12,26,27] the Ca 2+ transient declines faster at high preload. Superimposing of Ca 2+ transients obtained in rat cardiac muscle at low and high preload revealed their crossing on approximately half of the transient amplitude [16,17,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in ferret, cat and rat myocardium [18,22] and isolated Guinea-pig and rat myocytes [12,26,27] the Ca 2+ transient declines faster at high preload. Superimposing of Ca 2+ transients obtained in rat cardiac muscle at low and high preload revealed their crossing on approximately half of the transient amplitude [16,17,23].…”
Section: Introductionmentioning
confidence: 99%
“…Preload-dependent changes in calcium handling in cardiomyocytes are more complex and controversial. No preload-dependence of resting [Ca 2+ ] i level has been shown in ferret papillary muscle [8], mouse right ventricular trabeculae [9], and stimulated or quiescent Guinea-pig, rat and mouse cardiomyocytes [10][11][12][13][14]. On the other hand, preload caused a rise in resting calcium level in stimulated Guinea-pig right ventricular trabeculae [15] or a small significant decrease of that level in rat ventricular trabeculae [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in the literatures on single cardiac cells and whole hearts has shown that mechanical stretch can alter action potential duration (Zeng et al, 2000), and generate extrasystoles in isolated frog (Lab, 1978), pig (Dean and Lab, 1989) and dog (Hansen et al, 1990;Stacy et al, 1992) hearts. It has been speculated that this process of "mechanoelectric feedback" could alter the normal distribution of repolarization and excitability (Tung and Zou, 1995;White et al, 1993), and potentiate the likelihood for reentrant arrhythmia in failing hearts (Dean and Lab, 1989;Reiter, 1996). We are testing MEF effect experimentally using 2D cardiac cell monolayers, characterizing electrophysiological properties, such as excitability, refractoriness (action potential duration) and electrical conduction (conduction velocity) of the monolayer under different mechanical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As myocardiocytes were mechanically stretched, an outwardly rectifying K + current component with a conductance of approximately 100-130 pS was detected in whole-cell recordings in rat ventricular myocytes, and underlay the drop in refractoriness. The reduction in plateau and repolarization duration was induced by stretch, reported by Franz et al [31,33,34,38,39,47]. The shortening of plateau phase results from either of the two factors: the acceleration of K + outflow or the acceleration of Ca 2+ inflow.…”
Section: Tachyarrhythmogenesis In Stretchmentioning
confidence: 99%
“…Song et al [86] detailed the features: "In cornea and skin, a laterally oriented, wound-induced d.c. (direct current) electric field is generated instantaneously when the epithelium is damaged, and it persists until re-epithelialization restores the electrical resistance barrier function of the epithelium". These electric fields were estimated to be [40][41][42][43][44][45][46][47][48][49][50] , and spatial variations in the electrical resistance of epithelial sheets [86].…”
Section: The Identity Of Electric Field Lateralization Induced By Dismentioning
confidence: 99%